A feedback loop between GATA2-AS1 and GATA2 promotes colorectal cancer cell proliferation, invasion, epithelial-mesenchymal transition and stemness via recruiting DDX3X - Yuliang Pan; Yuxing Zhu; Jun Zhang; Long Jin; Peiguo Cao (Journal of Translational Medicine, 2022)
Abstract Background Colorectal cancer (CRC) is a common malignant tumor with a high risk of metastasis. Long non-coding RNAs (lncRNAs) have been reported to be implicated in cancer progression via regulating its nearby gene. Herein, we investigated the function of GATA binding protein 2 (GATA2) and lncRNA GATA2 antisense RNA 1 (GATA2-AS1) in CRC and the mechanism underlying their interaction. Methods Colony formation assay, flow cytometry analysis and transwell assay were implemented to detect cell proliferation, apoptosis and invasion. Western blot analysis and sphere formation assay were conducted to assess epithelial-mesenchymal transition (EMT) and cancer stemness of CRC cells. RNA pull down, RNA-binding protein immunoprecipitation (RIP), chromatin immunoprecipitation (ChIP) and luciferase reporter assays were implemented to investigate the regulatory mechanism between GATA2-AS1 and GATA2. Results GATA2-AS1 and GATA2 were highly expressed in CRC cells. Knockdown of GATA2-AS1 and GATA2 impeded CRC cell proliferation, invasion, EMT and cancer stemness, and induced cell apoptosis. GATA2-AS1 expression was positively correlated with GATA2. GATA2-AS1 recruited DEAD-box helicase 3 X-linked (DDX3X) to stabilize GATA2 mRNA. GATA2 combined with GATA2-AS1 promoter to enhance GATA2-AS1 expression. Conclusion Our study confirmed that a feedback loop between GATA2-AS1 and GATA2 promotes CRC progression, which might offer novel targets for CRC treatment.